2016
DOI: 10.1001/jamadermatol.2015.3903
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Efficacy of Anakinra in Severe Hidradenitis Suppurativa

Abstract: IMPORTANCE Hidradenitis suppurativa (HS) is a common skin disorder in which excessive inflammation is believed to have an important role. There is no specific therapy for HS. OBJECTIVE To investigate the safety and efficacy of the anti-inflammatory biological therapy anakinra in HS. DESIGN, SETTING, AND PARTICIPANTS Double-blind, randomized, placebo-controlled clinical trial with a 12-week treatment phase and a 12-week follow-up phase. The setting was Attikon University General Hospital, a tertiary care instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
177
0
8

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(200 citation statements)
references
References 29 publications
3
177
0
8
Order By: Relevance
“…However, in a recent double-blind, randomized, placebo controlled trial, 20 patients were treated with Anakinra or placebo daily for 12 weeks. HS clinical response after 12 weeks was 78% in Anakinra-treated patients versus 30% in the placebo group (ClinicalTrials.gov Identifier: NCT01558375) (Tzanetakou et al, 2016). …”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 99%
“…However, in a recent double-blind, randomized, placebo controlled trial, 20 patients were treated with Anakinra or placebo daily for 12 weeks. HS clinical response after 12 weeks was 78% in Anakinra-treated patients versus 30% in the placebo group (ClinicalTrials.gov Identifier: NCT01558375) (Tzanetakou et al, 2016). …”
Section: Skin Diseases With Il-1 Involvementmentioning
confidence: 99%
“…Furthermore, none of the trials reported the percentage of patients that were Hispanic or stratified the responses to adalimumab by race. The majority of the efficacy trials investigating other systemic agents, including etanercept, infliximab, anakinra, and ustekinumab, either did not report race or had largely Caucasian cohorts [37-40]. Taken together, this highlights the underrepresentation of non-Caucasian subjects and the need for trials that enroll more HS patients with SOC and stratify results by racial subgroups (Table 2).…”
Section: Treatment Response In Socmentioning
confidence: 99%
“…The current medical literature reports the effectiveness and desirability of treating HS with biological agents that inhibit TNF-α especially adalimumab and infliximab [26], but also others such as anakinra (anti-IL-1) [27] and ustekinumab (directed against IL-12 and IL-23) [28] may be a promising treatment strategy. Nevertheless further investigations are needed.…”
Section: Discussionmentioning
confidence: 99%